"Gestión administrativa financiera y su incidencia en la rentabilidad de la empresa Diventas. Período 2011-2012, Sistema de Gestión". - Fares Vargas, Freddy Jeovanny (2013)
Currently one of the problems faced by distributors of consumer goods, is the lack of strategies and ignorance in Administrative Management, on the grounds that the managers do not comply with the policies, purposes, principles, although they remain at a level acceptable sales, this will lead in the short or medium term that affects the profitability of the business. For this reason we conducted this research entitled "ADMINISTRATIVE AND FINANCIAL MANAGEMENT AND ITS IMPACT ON THE PERFORMANCE OF THE COMPANY DIVENTAS, PERIOD 2011-2012 MANAGEMENT SYSTEM”, a company dedicated to buying wholesale and retail of products mass consumption. The company develops in a competitive environment that requires that their results are permanently evaluated, which will meet business goals proposed. The research is focused on analysis of financial and administrative management of balances of accounts receivable and DIVENTAS company budget, in order to know the effectiveness of collection policies adopted by management to maintain high recovery of accounts receivable during the years 2011 and 2012. In the financial statements of the company DIVENTAS the month of January 2011 to December 2012, will analyze the balances of accounts receivable and its effect in the budget, this will apply procedures, methods and techniques for financial analysis the behavior and management of accounts receivable and accounts, variation, amounts, policies and management strategies currently applied collection. Within the enterprise management indicators DIVENTAS, after making the calculation of liquidity ratio determined to have $ 75 cents in 2011 and $ 76 cents in 2012, up 1 cent, has to cover the payment of their regular duties. The ratio of current assets inventory represents 23% is for 2011 and 4% by 2012 from current assets respectively Solvency index determined to have $ 0.96 in 2011 and $ 1.15 for 2012, which indicating the economic availability to cover short-term liabilities. In order to improve the current situation on the credit system management and collection process of the company, settled with law strategies billing department in order to recover the portfolios that are in arrears by lines of action and fixed responsibility competent staff, and was developed mission, vision, policies, strategies and indicators for evaluation and monitoring.